GERAK TARI PAYUNG DI SANGGAR IJUAK SAPILIN ENTERTAINMENT:KAJIAN BENTUK DAN STRUKTUR - Rahmadani, Fauziah; Indrayuda (Universitas Negeri Padang, 2025)
This study aims to describe the Form and Structure of the Payung Dance movements at Sanggar Ijuak Sapilin Entertainment. This research is qualitative with a descriptive method. The main instrument in this study is the researcher themselves, assisted by writing tools, a camera, and a voice recorder. Data is collected through literature review, observation, interviews, and documentation. The steps of data analysis are collecting data, presenting data, condensing data, and drawing conclusions from the data. The results show that the Ijuak Sapilin Payung Dance is a creative dance work that highlights the integration of traditional elements and innovation through the application of harmonious hierarchical and grammatical relationships.The hierarchical relationship in Tari Payung Ijuak Sapilin is apparent through the organized arrangement of movements from basic movements, motifs, phrases, to dance sentences that combine to form a complete dance composition. Each layer of movement is interconnected and functions to support the overall presentation of the dance. Meanwhile, in terms of grammatical relationships, Tari Payung Ijuak Sapilin shows two forms of relationships, namely syntagmatic and paradigmatic relationships. The syntagmatic relationship is seen in the movement motifs, where the sequence of movements is arranged linearly and continuously to form a logical flow. Meanwhile, the paradigmatic relationship appears at the phrase and movement sentence levels, where several parts can be exchanged in position without changing the overall meaning or message of the dance.